Construction and calibration of a goniometer to measure contact angles and calculate the surface free energy in solids with uncertainty analysis - Schuster, Jonathan Maximiliano (2018)
Here, we present the construction and calibration of a low-cost goniometer to measure contact angles by the sessile drop method. Besides, we propose a simple and fast method to calculate the uncertainty in the determination of the surface free energy (SFE) and its polar and dispersive components through the Owens-Wendt model and tested it by using two testing liquids. The goniometer performance and the SFE uncertainty were determined on two polymers: polytetrafluorethylene (PTFE) and polyoxymethylene (POM), by using water and methylene iodide. The values of contact angle measured were used to calculate the SFE and its components with their errors. The SFE values obtained for PTFE were 17.57–17.91 mJ/m2, with a relative error lower than 5.5%, whereas those for POM were 42.80–43.23 mJ/m2, with a relative error lower than 4.3%. Both the SFE values and the errors were in the range of those previously reported. Based on the mathematical analysis of the uncertainty propagation in the determination of SFE, we concluded that the uncertainty is minimized when the testing liquids are an apolar liquid and water.